Assessment Of Management Strategies In Alcoholic Liver Disease Patients With Hypertension Or Diabetes Mellitus - Sanjaykumar, Dave Vansh; Patel, Harsh P; Machhar, Rohit Kumar; Patel, Nivedita; Shah, Zalak C.; Chakraborthy, GS (Journal of Neonatal Surgery, 2025)
Objective: Analysis of different Treatment Strategies in ALD with Hypertension & ALD with Diabetes Mellitus and its Prescription Patterns Assessment with Comparison study of Alcoholic liver disease or Alcoholic Liver Disease with Hypertension or Diabetes Mellitus. To learn about the specific treatments given in patients of ALD Methods: A retrospective observational analysis was conducted in a tertiary care center. The data of the patients undergoing treatment for ALD with hypertension or diabetes mellitus were obtained. Patients with ALD undergoing therapy. Data of 100 patients was gathered and examined from the Parul Sevashram Hospital. The data was reported and analyzed using graphical, chart, figures, and tabulations, and it was visually summarized in the data collection analysis form. Results: Among 100 patients, 97% of patients were prescribed with oral ursodeoxycholic acid in both ALD with Hypertension & ALD with Diabetes mellitus. Furthermore, Oral Spironolactone was prescribed in 95% Patients for the treatment. And it was followed by Rifaximin & intravenous Human Albumin in some patients. It has also been noticed that oral Lactulose, intravenous Furosemide & various other supplements have been prescribed majorly in ALD alongside. Conclusion: Ursodeoxycholic acid, which is an Hepatoprotective Agent, Spironolactone which is an Aldosterone receptor antagonist, Rifaximin which is an antibiotic are majorly used in the treatment of this ailment. However more research and large sample size is required for the assessment of management of the following.